Meta-Analysis of the Effect of Exercise on Neuropathic Pain Induced by Peripheral Nerve Injury in Rat Models - Guo, Jia-bao; Chen, Bing-lin; Wang, Ying; Zhu, Yi; Song, Ge; Yang, Zheng; Zheng, Yi-li; Wang, Xue-qiang; Chen, Pei-jie (Frontiers in Neurology, 2019)
Background: There is accumulating evidence showing that exercise therapy may play an active role in peripheral neuropathic pain (NP). However, there have been no meta-analysis to investigate the effects of exercise on NP induced by peripheral nerve injury in rat models. Methods: PubMed, EMBASE, and Web of Science were searched from inception to January 2019. A random-effect model was implemented to provide effect estimates for pain-related behavioral test outcome. Mean differences (MDs) with 95% confidence intervals (CIs) were calculated. Results: Fourteen studies were included. For the mechanical withdrawal threshold, rats in the exercise group exhibited significantly lower thresholds than those in the control group, with a MD of 0.91 (95% CI 0.11 to 1.71), 3.11 (95% CI 1.56 to 4.66), 3.48 (95% CI 2.70 to 4.26), 4.16 (95% CI 2.53 to 5.79), and 5.58 (95% CI 3.44 to 7.73) at 1, 2, 3, 4, and 5 weeks, respectively. Additionally, thermal withdrawal latency decreased in the exercise group compared with the control group, with a MD of 2.48 (95% CI 0.59 to 4.38), 3.57 (95% CI 2.10 to 5.05), 3.92 (95% CI 2.82 to 5.03), and 2.84 (95% CI 1.29 to 4.39) at 1, 2, 3, and 4 weeks, respectively. Subgroup analyses were performed for pain models, exercise start point, exercise forms, and duration, which decreased heterogeneity to some extent. Conclusion: This meta-analysis indicated that exercise inhibited mechanical withdrawal threshold and thermal withdrawal latency in animal NP models. Exercise therapy may be a promising non-pharmacologic therapy to prevent the development of NP. Further preclinical studies focused on improving experiment design and reporting are still needed.